Camponeses órfãos : farinheiros de Ribeirópolis e São Domingos-SE - 1975-2005 - Jesus, Givaldo Santos de (2006)
The study analyzes the organization, the production and the units peasants' reproduction in the municipal districts of Ribeirópolis and São Domingos-SE, connected to the general product system of goods in the trajectory 1975 - 2005. In the two municipal districts a high land concentration verified due to the insertion of the capital in the field, and with an economy turned back to the external market, becoming necessary the amplification of the grass for the cattle creation, assisting to the interests of the capital. Though, the more the capitalism moves forward, at the same time that, persists the unit productive peasant that resists the with the using by force of family work, cultivating the cassava, the corn and the bean, besides the small raise rear. The cassava with the processing of the flour and the commercialization of its surplus became one of the fundamental elements of the reproduction and resistance of that peasant workers in the field. The units of production possess a low modernization level, because the traditional techniques of production still prevail with the using of instruments of handmade work as the hoe and pesticides for the combat to the ants and plagues. For analysis effect, the peasant field of the two municipal districts was divided in partial " peasants " and exclusive " peasants ". The partial ones characterize for little land and it doesn't produce enough for its reproduction, needing complementary the family income selling manpower. However, considered them exclusive they possess area of enough land to produce and to guarantee its survival without appealing to the rented work. However, the subordination of the peasant workers to the capital is still very strong, and the omission of the State generates what we denominated of orphan " peasants " of the public politics joining a series of problems faced by the peasant workers, for example of the productive chain that is disjointed in the two municipal districts favoring the middlemen's action in the commercialization of the cassava flour. Actually it is in the phase of the circulation that the capital subordinates and appropriates itself of the surplus of the work of the peasant workers, reproducing a contradictory system, and appropriates itself of the surplus of the work of peasant works , where for one hand subordinates the work of flour-man peasant the circulation and, on the other hand it resists, in that characteristics as affection to the land, exclusive use of forcing by the family work and control of the necessary work, they still persist.